2019
DOI: 10.1016/j.watres.2019.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Structural dynamics and transcriptomic analysis of Dehalococcoides mccartyi within a TCE-Dechlorinating community in a completely mixed flow reactor

Abstract: A trichloroethene (TCE)-dechlorinating community (CANAS) maintained in a completely mixed flow reactor was established from a semi-batch enrichment culture (ANAS) and was monitored for 400 days at a low solids retention time (SRT) under electron acceptor limitation. Around 85% of TCE supplied to CANAS (0.13 mmol d −1) was converted to ethene at a rate of 0.1 mmol d −1 , with detection of low production rates of vinyl chloride (6.8 × 10− 3 mmol d −1) and cisdichloroethene (2.3 × 10− 3 mmol d −1). Two distinct D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 81 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…This study suggested a strain-level discrepancy between the Cryptococcus fungal species and their in-situ mock communities. Thus, transcriptomic analysis provides a large amount of gene information about the potential function of microbial communities in adaptation and survival in extreme environments (Singh D. P. et al, 2018 ; Mao et al, 2019 ; Marcelino et al, 2019 ).…”
Section: Recent Advanced Technologies Employed In Bioremediation For mentioning
confidence: 99%
See 1 more Smart Citation
“…This study suggested a strain-level discrepancy between the Cryptococcus fungal species and their in-situ mock communities. Thus, transcriptomic analysis provides a large amount of gene information about the potential function of microbial communities in adaptation and survival in extreme environments (Singh D. P. et al, 2018 ; Mao et al, 2019 ; Marcelino et al, 2019 ).…”
Section: Recent Advanced Technologies Employed In Bioremediation For mentioning
confidence: 99%
“…Therefore, the study of microbial population existing in contaminated environments provides a significant knowledge of specific microbial characteristics that improve degradation rates. However, effective implementation of microbial remediation strategies needs advanced technical approaches, which provide an in-depth understanding about the dynamics aspects of microbial activity and survival under stressed environment (Rastogi and Sani, 2011 ; Lima-Morales et al, 2016 ; Mao et al, 2019 ). The development in molecular, biotechnological, bioinformatics and system biology tools pertaining to bio-remedial problems have provided gene level mechanisms of bioremediation (Ahmad and Ahmad, 2014 ; Aora and Bar, 2014 ; Singh D. P. et al, 2018 ; Jaiswal and Shukla, 2020 ; Nkongolo and Kotha, 2020 ; Wolf et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more efforts should be devoted to exploring the actual mechanisms of anaerobic reductive dechlorination. Overall, pceA , tceA (TCE to DCE), tceA , dceA , vcrA , bvcA (cis-DCE to VC), and tceA , vcrA , bvcA (VC to ethene) are crucial RDases involved in TCE reductive dechlorination process ( Figure 2B ; Ise et al, 2011 ; Popat and Deshusses, 2011 ; Dugat-Bony et al, 2012 ; Zinder, 2016 ; Dolinova et al, 2017 ; Mao et al, 2019 ; Yan et al, 2021 ; Rossi et al, 2022b ). Furthermore, the recently discovered new strain Dehalococcoides mccartyi NIT01 contains 19 rdhA genes (including NIT01 - rdhA7 and rdhA13 ), which are basically the same as the encoded vcrA and pceA ( Asai et al, 2022 ).…”
Section: Biodegradation Of Tcementioning
confidence: 99%
“…This study suggested a strain-level discrepancy between the Cryptococcus fungal species and their in-situ mock communities. Thus, transcriptomic analysis provides a large amount of gene information about the potential function of microbial communities in adaptation and survival in extreme environments (Singh D. P. et al, 2018;Mao et al, 2019;Marcelino et al, 2019).…”
Section: Sato Et Al 2019mentioning
confidence: 99%
“…Therefore, the study of microbial population existing in contaminated environments provides a significant knowledge of specific microbial characteristics that improve degradation rates. However, effective implementation of microbial remediation strategies needs advanced technical approaches, which provide an in-depth understanding about the dynamics aspects of microbial activity and survival under stressed environment (Rastogi and Sani, 2011;Lima-Morales et al, 2016;Mao et al, 2019). The development in molecular, biotechnological, bioinformatics and system biology tools pertaining to bioremedial problems have provided gene level mechanisms of bioremediation (Ahmad and Ahmad, 2014;Aora and Bar, 2014;Singh D. P. et al, 2018;Nkongolo and Kotha, 2020;Wolf et al, 2020).…”
Section: Introductionmentioning
confidence: 99%